(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2024)
Poland is a country where Muslims constitute a small minority. Although official and unofficial estimates differ significantly, the size of Muslim community does not exceed 0.5% of the total population. The institutionalized religious life of Muslims in Poland takes place primarily within two religious associations – the Muslim Religious Union and the Muslim League in the Republic of Poland. Polish Muslims, looking for opportunities to create a community and belong to it do this mainly outside the institutional sphere; they meet in informal groups. In order to acquire religious knowledge and develop their spiritual life, they use various religious sources – including the Internet. In recent years, the practice of sharing khutbas online in a form of text or video recordings has become increasingly popular. In this paper we focus on the khutbas delivered in three masjids run by three different organizations – the Muslim Religious Union, the Muslim League in the Republic of Poland and the Sakinah Foundation. We use elements of content analysis and thematic analysis to answer the following questions: 1) how do khutbas convey Islam to the faithful – is it a teaching of the principles of faith, or rather a message that is intended to stimulate faith, emotions and moral dispositions related to Islam; which of these elements are most emphasized; 2) how khutbas fit into the Polish cultural context at the lexical and content level; and 3) whether and to what extent the khutbas delivered in Polish mosques raise socio-political issues and therefore go beyond the par excellence religious themes?